"They said I'm a square for eating them": Children's beliefs about fruit and vegetables in England. Issue 12 (5th December 2016) - Povey, Rachel; Cowap, Lisa; Gratton, Lucy
Abstract : Purpose: The purpose of this paper is to explore primary school children's beliefs towards eating fruit and vegetables in a deprived area in England. Design/methodology/approach: Semi-structured interviews were conducted with 11 children aged 9-11 from an after school club at a primary school in a deprived area in the West Midlands. Interviews were analysed using inductive thematic analysis. Findings: Six master themes emerged from the data: "effect on the senses", "feelings about food", "healthy vs unhealthy foods", "effects on health", "convenience" and "family and friends". Analysis showed that children seemed to have a very good awareness of the health benefits of eating fruit and vegetables. However, negative beliefs were associated with sensory perceptions (such as taste, texture, appearance and aroma), availability, and the competing desirability of other, unhealthy foods. Also, although parents were key influences, siblings and friends were often perceived as negative influences and would tease children about eating fruit and vegetables. Practical implications: Suggestions for interventions include increasing the appeal and availability of pre-prepared fruits and vegetables in both home and school environments. Additionally, an approach to eating more fruit and vegetables which focusses on siblings and friends is advocated as these groups appear to play a key role in terms of promoting the consumption of these foods. Originality/value: This study is novel as it uses individual interviews to explore primary school children's attitudes towards fruit and vegetable consumption in a deprived area in England. By focussing on the specific behaviours of fruit and vegetable consumption, the findings aid the development of interventions that are designed to improve children's healthy eating behaviour.